The Role of Anemia and Thrombotic Risk Factors in Pregnancy Complications (Global Journal of Medical Research, 2021)
In a case-control study of 454 pregnancy and delivery cases, women with and without thrombotic risk factors showed different effects of anemia on pregnancy. In women with risk factors and anemia, miscarriage was significantly less common than in patients without anemia. High hemoglobin levels in the 1st trimester were associated with an increased risk of preeclampsia in the same group. Middle and severe anemia was associated with preterm birth, and also with placental insufficiency in women with thrombotic risk factors. Iron supplementation for mild anemia without confirmed iron deficiency may trigger urinary tract infections in pregnant women.
Keywords: #x430; #x43D; #x435; #x43C; #x438; #x44F; #x431; #x435; #x440; #x435; #x43C; #x435; #x43D; #x43D; #x43E; #x441; #x442; #x44C; #x43F; #x440; #x435; #x44D; #x43A; #x43B; #x430; #x43C; #x43F; #x441; #x438; #x44F; #x43D; #x435; #x432; #x44B; #x43D; #x430; #x448; #x438; #x432; #x430; #x43D; #x438; #x435